A krízishelyzetek hatása és kihívásai a kárpátaljai magyarok oktatására 2017-2023 között - Orosz Ildikó; Орос Ільдіко; Oros Ildiko (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Ukrajna Oktatási és Tudományos Minisztériuma 2015-ben dolgozta ki az oktatás fejlesztésének 2015–2025 között megvalósuló koncepcióját, melynek eredményeként új oktatási törvényt hagyott jóvá a parlament az új ukrán iskolamodell bevezetése céljából. A 2017‒2023 között megvalósuló törvényalkotási folyamatok eredményeként a nemzeti kisebbségek csak 5. osztályig tanulnak anyanyelvükön, a későbbi iskolafokokon az oktatás nyelvét fokozatosan átveszi az államnyelv. Ezzel párhuzamosan előtérbe került az angol nyelv tanításának igénye, melyre az európai oktatási térben való érvényesülés eszközeként tekintenek. Mindezek a folyamatok, a világjárvánnyal és háborús helyzettel terhelve új oktatási stratégiák keresésére ösztönözték az érintetteket.

Abstract. In 2015, the Ministry of Education and Science of Ukraine developed the 2015-2025 Concept of Education Development, which resulted in the Parliament’s approval of a new Law on Education aiming at the introduction of the new Ukrainian school model. As a result of the legislative processes between 2017 and 2023, national minorities will only learn in their mother tongue up to grade 5, with the state language gradually taking over the language of instruction at the next school education levels. At the same time, the need to teach English, which is seen as a means of gaining a foothold in the European educational space, has come to the foreground. These developments, coupled with the pandemic and the war situation, have encouraged those involved to seek new educational strategies. The Ministry of Education and Science of Ukraine by its Decree No.1033 of 29.09.2021 approved a pilot project for the years 2021-2026 for the Hungarian-language schools in Transcarpathia entitled European Integrated School Model for the Hungarian-language Secondary Education Institutions in Transcarpathia in 2021-26.
The impact and challenges of crisis situations on the education of hungarians in Transcarpathia between 2017-2023
Keywords: krízishelyzet; anyanyelvi oktatás; oktatási stratégiák; megküzdési lehetőségek